Diseño de una planta para la recuperación y procesamiento de co2, obtenido en destilerias de alcohol. - Cabrera Cabrera, Stiwar Orlando (2012)
Chapter I Is carried out succinctly the study corresponding to the supply and demand for CO2 in Peru market. This study was based on statistical data related to the consumption of CO2 in Peru, basically taking into account the CO2 as a product is new and therefore has little historical data regarding consumption. Chapter II Deals with the description of the process and is based on the German BUSE technology, as CO2 to recover and process technology is import and BUSE is one of the pioneers in this area. Chapter III It aims to determine the choice of the most suitable place for installing the plant, for this use of the technique known as balancing factors, which consists assign numerical values to different factors both primary and secondary values is made. Chapter IV It includes the design of major equipment such as absorbers, Flash separators, compressors and tanks. For the design of the first four Hysys 3.0.1 the simulator is used, while for the case of tanks using the EXCEL spreadsheet done. Chapter V This chapter refers to the part of the instrumentation and automatic control, here defined the type of control to use and illustrate both control loops used. Chapter VI This chapter deals with processing aids such as water, fuel and electricity; also it includes storage facilities, security, and laboratory buildings. Chapter VII Deals with the distribution of the plant and basically defines the spatial arrangement of all operating units, for which the unit and master plan were developed. Chapter VIII This chapter provides an economic study is carried out to determine the profitability of the project. Chapter IX In this chapter the conclusions of the study are presented. Chapter X Sample references. Chapter XI In the appendix, which are developed in detail Chapter 4 and Chapter 8 tables detailing is presented.